Morphine treatment alters nucleotidase activities in rat blood serum - Rozisky JR; Nonose Y; Laste G; dos Santos VS; de Macedo IC; Battastini AM; Caumo W; Torres IL (Dove Medical Press, 2012)
Joanna Ripoll Rozisky,1,2,4,* Yasmine Nonose,1,4,* Gabriela Laste,1,2,4 Vinicius Souza dos Santos,1,4 Isabel Cristina de Macedo,1,2,4 Ana Maria Oliveira Battastini,2,3 Wolnei Caumo,2,4 Iraci LS Torres1,2,41Laboratório de Farmacologia da Dor e Neuromodulação: Modelos Animais, Departamento de Farmacologia, Instituto de Ciências Básicas da Saúde, 2Programa de Pós-Graduação em Medicina, Ciências Médicas, 3Departamento de Bioquímica, Instituto de Ciências Básicas da Saúde, Universidade Federal do Rio Grande do Sul, Rio Grande do Sul, Brazil; 4Unidade de Experimentação Animal e Grupo de Pesquisa e Pós-Graduação, Hospital de Clínicas de Porto Alegre, Rio Grande do Sul, Brazil *Both authors contributed equally to this workAbstract: Morphine has been widely used in neonatal pain management. However, this treatment may produce adaptive changes in several physiologic systems. Our laboratory has demonstrated that morphine treatment in neonate rats alters nucleoside triphosphate diphosphohydrolase (NTPDase) activity and gene expression in central nervous system structures. Considering the relationship between the opioid and purinergic systems, our aim was to verify whether treatment with morphine from postnatal days 8 (P8) through 14 (P14) at a dose of 5 µg per day alters NTPDase and 5´-nucleotidase activities in rat serum over the short, medium, and long terms. After the in vivo assay, the morphine group showed increased hydrolysis of all nucleotides at P30, and a decrease in adenosine 5´-diphosphate hydrolysis at P60. Moreover, we found that nucleotidase activities change with age; adenosine 5´-triphosphate hydrolysis activity was lower at P16, and adenosine 5'-monophosphate hydrolysis activity was higher at P60. These changes are very important because these enzymes are the main regulators of blood nucleotide levels and, consequently, nucleotide signaling. Our findings showed that in vivo morphine treatment alters nucleotide hydrolysis in rat blood serum, suggesting that purine homeostasis can be influenced by opioid treatment during the neonatal period.Keywords: 5´-nucleotidase, morphine, neonate, NTPDase, rat blood serum